Postoperative radiotherapy with an electron beam on keloid scar: epidemiological evaluation in a teaching hospital - DE MENEZES-NETO, Balduino Ferreira [UNESP]; Magnani, Lucas Vannuchi [UNESP]; DE OLIVEIRA JÚNIOR, Batista [UNESP]; Palhares Neto, Aristides Augusto [UNESP] (Thieme, 2023)
Introduction: Keloids are one of the most aggressive spectrums of healing disorders. They have a unique pathophysiology and multiple specific genetic and cellular factors, which have not yet been fully elucidated. So far, literature reviews have found the influence of genetics, injury site, and ethnicity on the incidence and rate of recurrence. Furthermore, the need to associate an adjuvant method with surgical excision has already been verified, but the best therapy has yet to be defined. Method: A retrospective analysis of medical records was carried out to assess the profile of patients who underwent postoperative radiotherapy with an electron beam to treat keloids at the Hospital das Clínicas da Faculdade de Medicina de Botucatu between 2015 and 2019. Results: Data from 131 patients were evaluated, with 269 keloid scars treated. The average duration of treatment was 51 days, and the number of sessions was 17. White patients were predominant (78%) and women (70%), with surgical incision being the main cause of formation (49%) and ear the most identified location (33%). Women were more likely to complete the proposed treatment (p=0.04), while non-literates completed less than those who had at least completed primary or secondary education (p<0.0001). Conclusion: Postoperative radiotherapy for keloid scars is a well-established treatment in the literature and an important tool for plastic surgeons. Knowing the profile of patients who need this therapy is essential to create methods that improve adherence and results.
Radioterapia pós-operatória com feixe de elétrons sobre cicatriz queloideana: avaliação epidemiológica em hospital de ensino
Keywords: Keloid; Medical records; Radiotherapy, adjuvant; Reconstructive surgical procedures; Scar